Comparing mathematics teachers’ beliefs about good teaching: the cases of Estonia, Latvia and Finland - Lepik, Madis; Pipere, Anita; Hannula, Markku S. (NOMAD Nordic Studies in Mathematics Education, 2012)
The article presents results from a cross-cultural NorBa project Mathematics teachers’ educational beliefs. We report on Estonian, Latvian and Finnish lower secondary mathematics teachers’ espoused beliefs about good teaching. A principal component analyses identified a two-component structure of teachers’ beliefs about good teaching: (1) Reasoning and conceptual understanding and (2) Mastery of skills and facts. Cross-cultural differences were identified in both of these dimensions. Latvian teachers indicated the strongest agreement with reasoning and conceptual understanding, Estonian teachers with mastery of skills and facts, while Finnish teachers scored lowest on both dimensions. Moreover, we analysed the amount of teachers with different profiles with regard to these two dimensions. The results suggest both common conceptual core of teachers’ beliefs on mathematics teaching and certain cultural influence on the profile of these beliefs.